Effects of Light Environments on Leaf Traits and Phenotypic Plasticity of Canna indica - Yorianta Hidayat Sasaerila; Sakinah Sakinah; Nita Noriko; Risa Swandari Wijihastuti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Canna indica L (African arrowroot), is a beneficial, multi-use tropical perennial with a worldwide distribution, but relatively unexplored. This plant has the potential to be developed as a food crop in an intercropping system, utilizing idle land under commercial plantations such as rubber or teak. This study aimed to determine the best light-growing conditions for C. indica. A completely randomized design was used with growth light as the treatment consisting of 25%, 50%, and 100% of natural light, respectively. Leaf traits, growth characteristics, and phenotypic plasticity were used to measure C. indica’s response to different treatments. The results of this study showed that C. indica grown in low light has the best growth with increased height, leaf area, root and shoot dry weights, but decreased leaf thickness, which caused the increase in specific leaf area, leaf area ratio, and leaf weight ratio, but decreased root to shoot ratio. Based on leaf traits and biomass allocation, the phenotypic plasticity index was 0.23, a typical number for shade tolerant species. These findings were the first time to be reported for C. indica. For agroforestry practices, it can be recommended that C. indica be used as an intercropping plant under tree canopies.